Positive temperature coefficient (PTC) semiconductor ceramic composition, method for producing semiconductor ceramic, heating device and use

By introducing specific doping elements into BaTiO3 ceramics, the breakdown voltage and self-regulation performance of PTC ceramics are improved, and the problem of insufficient ceramic performance under high voltage is solved, and efficient heating element design is achieved, which extends battery life and reduces Manufacturing cost.

CN119306491APending Publication Date: 2025-01-14MAHLE INT GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410927226.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2024-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing PTC semiconductor ceramics cannot operate effectively at high voltages in the high voltage range, and the increase in component thickness to achieve high breakdown voltages leads to problems such as cost and air resistance.

Method used

Using the semiconductor ceramic composition based on BaTiO3, the compound is adjusted by co-doping of doped elements such as Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb and V, Nb. The chemical composition of the product improves breakdown voltage and self-regulation performance, and avoids increasing component thickness.

Benefits of technology

Good self-regulation and high breakdown voltages in the high voltage range are achieved, reducing component weight and air resistance, extending battery life and vehicle activity radius, while reducing manufacturing costs and energy requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306491A_ABST
    Figure CN119306491A_ABST
Patent Text Reader

Abstract

The invention relates to a composition for a semiconductor ceramic, said composition having, as a main component, a BaTiO3-based compound according to the following molecular formula: [BabCacSrsPbpRx] [TitAaMnm] O3 + z, where R is at least one element selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, where A is at least one element selected from the group consisting of V, Nb and Ta, where z is at least one element selected from the group consisting of V, Nb and Ta. The variables b, c, s, p, x, t, a, m and z are defined in the following manner: b = 1-c-s-p-x0lt; c + s + plt; the method comprises the following steps of: obtaining 0.510.490 Blt; 0.9999. 0 lt, 0.9999. 0 lt; clt; ct; 0.50.0 lt, 0.50.0 lt; slt; the volume is 0.5 to 0.05 lt; plt; the volume of the catalyst is 0.50.001 lt; xlt; the invention relates to a method for preparing a high-purity magnesium alloy. (t + a + m) lt; 1.0115750.9889 lt, tlt; 1.0003750.00010 lt, a < lt >; the method comprises the following steps: (1) carrying out heat preservation; mlt; mlt; the content of the compound is 0.01 to 0.0001 lt; zlt, zlt; 0.01, to a method for producing a corresponding PTC semiconductor ceramic, to the use of a PTC semiconductor ceramic, and to a heating device having a PTC semiconductor ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a PTC semiconductor ceramic composition, a method for producing a corresponding PTC semiconductor ceramic, a use of a PTC semiconductor ceramic and a heating device having the PTC semiconductor ceramic according to the generic nature of the independent claims. Background Art

[0002] The electrical conductivity of semiconductor ceramics decreases as the temperature increases due to the increase in resistance, and the semiconductor ceramics show thermal self-regulation, which can be used when used as heating elements. This effect is also called the PTC effect (Positive Temperature Coefficient). Since the waste heat generated in the motor can be used to heat the interior space in motor vehicles with internal combustion engines that have been mainly used so far, PTC heating elements have been used in the past only as additional heating devices for rapid heating or in the case of cold external temperatures. Such additional heating elements are usually designed for on-board power systems in the low-voltage range (typically with a voltage of up to 48 volts). For example, DE 102014 110 164 A1 relates to a heating device with a PTC heating resistor and a method for manufacturing a heating rod, which can be used to heat the passenger interior.

[0003] However, in electric vehicles, there is no waste heat from the internal combustion engine to use. Nevertheless, heat is needed not only for temperature control of the vehicle interior, but also for temperature control of the battery. In addition, in electric vehicles, significantly higher onboard power supply voltages are used. For example, in passenger cars, onboard power supply voltages of up to 350 volts are used nominally, and in the medium term, efforts are being made to reach voltages of 800 volts nominally (high voltage range). This is mainly based on the following: the increased voltage shortens the battery charging time or increases the available battery life and the power density can also be increased. The PTC components used in the past either could not meet these voltage requirements or could only meet these voltage requirements by using significantly larger component thicknesses. Summary of the invention

[0004] The object of the present invention is to indicate new ways in the development of a PTC semiconductor ceramic composition for a PTC semiconductor ceramic and a corresponding method for producing the ceramic and a corresponding heating device in order to improve the thermal and / or electrical properties thereof.

[0005] This object is achieved according to the invention by the subject matter of the independent claim. Advantageous embodiments are the subject matter of the dependent claims.

[0006] According to the present invention, there is provided a semiconductor ceramic composition, wherein the semiconductor ceramic composition has as a main component a BaTiO3-based compound according to the following molecular formula

[0007] [Ba b Ca c Sr s Pb p R x ][Ti t A a Mn m ]O 3+z ,

[0008] wherein R is at least one element selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb,

[0009] wherein A is at least one element selected from the group of V, Nb, and Ta, wherein variables b, c, s, p, x, t, a, m, and z are defined as follows:

[0010] b=1–c–s–p–x

[0011] 0 <c+s+p<0.51

[0012] 0.490 <b<0.999

[0013] 0.0 <c<0.5

[0014] 0.0 <s<0.5

[0015] 0.05 <p<0.5

[0016] 0.001 <x<0.01

[0017] 1.0001<(t+a+m)<1.011575

[0018] 0.9889 <t<1.000375

[0019] 0.00010 <a<0.0012

[0020] 0.0001 <m<0.01

[0021] 0.0001 <z<0.01。

[0022] Compared to the prior art, the semiconductor ceramic composition according to the invention having the features of independent claim 1 has the following significant advantages: it has a high breakdown voltage and good self-regulation and thus enables use in heating elements for operation at high voltages up to the high voltage range. At the same time, there is no need to increase the component thickness excessively.

[0023] In the context of the present invention, the breakdown voltage of a PTC ceramic is understood to be the voltage at which, after reaching a constant current, the voltage further increases above U in the regulation range of the material. max A sudden increase in the current can be observed, which leads to irreversible damage to the ceramic. Figure 1 At the same time, PTC ceramics have the following characteristics: their resistance increases suddenly at a certain temperature. This allows self-regulation, because an increased current also leads to a higher temperature, whereby the resistance of the material increases and the current flow decreases. The breakdown voltage can be influenced not only by the material thickness, but also by the material composition itself. This will be discussed in more detail later.

[0024] Therefore, a further significant advantage is that a heating element based on the semiconductor ceramic composition according to the invention can be operated directly on the vehicle voltage even when a higher vehicle voltage is used. This avoids costs and sources of error, since expensive fuses and control technology, for example for switching to a lower voltage range, are not required.

[0025] Furthermore, a heating element based on the semiconductor ceramic composition according to the invention has the following significant advantages: For a high breakdown voltage, no excessively large component thickness is required. This makes it possible to avoid a high component weight. Furthermore, a high air resistance due to a large component thickness when used in a heating blower with an associated air duct can also be avoided. Furthermore, a high material requirement and the corresponding increased costs and increased energy requirement during production can be avoided. Furthermore, thermal stresses in the material and the resulting wear due to the large component thickness are significantly reduced.

[0026] Furthermore, the use of a heating element based on the semiconducting ceramic composition according to the invention allows for optimal temperature control of the battery in the charging state and in the driving state. Alternatively, however, the heating element can also advantageously be used only as an interior heating device, wherein lower air performance is required due to the advantageous savings in weight and size of the ceramic.

[0027] This results in a further significant advantage: the service life of the battery and the corresponding range of motion of the vehicle can be significantly increased.

[0028] This is achieved in particular by specifying a semiconductor ceramic composition with which a high breakdown voltage can be achieved while achieving good self-regulation.

[0029] The semiconductor ceramic composition according to the invention, a method for producing a PTC semiconductor ceramic or a corresponding sintered body, a use of a PTC semiconductor ceramic and a heating device having a PTC semiconductor ceramic are explained in more detail below, wherein the explanation of the ceramic according to the invention and the figures used in this context within the scope of the present invention also applies accordingly to the method and the use and the figures used in this context, and vice versa.

[0030] The invention is based on the general idea of ​​providing a semiconductor ceramic which has a steep rise in its resistance in its Curie temperature range and a high breakdown voltage and is also suitable for use in the high voltage range up to the high voltage range without having to excessively increase the thickness of the ceramic used. Since PTC components should generally also have a safety factor for the breakdown voltage, the breakdown voltage is generally limited to approximately twice the onboard power supply voltage. Thus, in the case of an onboard power supply voltage of 350 volts, a breakdown voltage of at least 650 volts is required, and in the case of an onboard power supply voltage of 800 volts, even a breakdown voltage of 1400 volts is required.

[0031] Typically, in the range of phase transition, such a strong resistance increase effect of the PTC ceramic occurs. In the case of a temperature significantly lower than the phase transition, there is a typical NTC (Negative Temperature Coefficient) semiconductor characteristic, that is, the resistance decreases with increasing temperature. In the range after the strong increase in resistance, there is also a typical NTC semiconductor characteristic. The special effect of the strong PTC resistance increase between the two NTC ranges and the strong current reduction under the given voltage can be used for the self-regulation of the heating element, because it prevents the power output of the heating element from always continuing to increase with the increase in current until, for example, combustion finally occurs.

[0032] The PTC effect occurs, for example, in compounds based on BaTiO3 and is a grain boundary effect coupled with a phase transition. Pure BaTiO3 has a phase transition from a tetrahedral crystal structure to a cubic crystal structure at about 120°C (the so-called Curie temperature). The cubic crystal structure of BaTiO3 is a typical example for an ideal cubic perovskite structure (Perowskit-Struktur). In this cubic crystal structure, the titanium (IV) cation is located at the center of an octahedron whose angles are constructed by oxide ions. The barium (II) cation is located at the center of a cubic octahedron constructed by oxide ions. In the case of compounds with other components, it is also conceivable that other cations and anions with charges different from the ionic charges mentioned here appear. Distortions occur in the tetrahedral structure, wherein deviations from the ideal octahedral geometry of the octahedron surrounding the Ti (IV) cation are mainly observed. As a result, the titanium (IV) cation is no longer located exactly at the center of the octahedron, the charge centers of Ti and O do not overlap each other, and BaTiO3 is a ferroelectric in a modification of the tetrahedral distortion (see below). This is no longer the case in the Cube variant.

[0033] Pure BaTiO3 has a band gap of about 3eV and therefore has low electrical conductivity. Therefore, doped BaTiO3 is typically used. Doping is understood to be the introduction of foreign atoms into the basic material. For example, the number of valence electrons that such foreign atoms have is different from the number of valence electrons of the corresponding elements of the basic material. Usually, BaTiO3 is doped with donor foreign atoms, which means, for example, that atoms with three valence electrons are introduced into the barium position, while the barium atom itself has only two valence atoms. But it is also possible to replace Ti with four valence atoms by pentavalent elements, which also means donor doping. By sintering under high oxygen partial pressure, barium vacancies and oxygen vacancies can be formed at the same time, and the concentration of the barium vacancies and oxygen vacancies is the highest on the grain boundaries. In this context, vacancies are understood to be that the position actually set for an element at this position in the crystal structure remains empty. If, for example, the material in ceramics exists in a polycrystalline form, the material contains many grain boundaries, which, for example, separate individual crystallization regions with different orientations from each other. The introduced vacancies can now act as acceptors, since the valence atoms of the elements normally present at this site are missing. In its quadrilateral shape, i.e. at normal pressures below 120° C., BaTiO3 is a ferroelectric, i.e. it can construct regions with the same polarization direction. The resulting polarization charges can compensate for the negative grain boundary charges due to the vacancies mentioned above. By means of the conversion to a cubic crystal structure, the ferroelectric properties are eliminated. The negative grain boundary charges can now no longer be compensated by polarization charges, but instead need to be compensated by donors, which are introduced by doping. As a result, at the phase transition temperature, the resistance first rises suddenly.

[0034] Now, the semiconductor ceramic composition according to the present invention has as a main component a compound based on BaTiO3 according to the following molecular formula: [Ba b Ca c Sr s Pb p R x ][Ti t A a Mn m ]O 3+z .

[0035] Here, the main component is understood to be the compound that is mainly present. It should be understood that such a semiconductor ceramic component can have small amounts of impurities with other compounds. For example, it is conceivable that such a semiconductor ceramic component can contain a small amount of impurities with reactants (such as TiO2 or BaCO3), especially less than 0.5 weight percent relative to the total components. It is also conceivable that the semiconductor ceramic component can contain a small amount of sintering aids, especially less than 5 weight percent relative to the total components. For example, the sintering aid is added in order to achieve a lower sintering temperature.

[0036] In the molecular formula of the main component of the semiconductor ceramic composition according to the present invention, R is at least one element selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb. A is at least one element selected from the group consisting of V, Nb and Ta, wherein the variables b, c, s, p, x, t, a, m and z are defined as follows:

[0037] b=1–c–s–p–x

[0038] 0 <c+s+p<0.51

[0039] 0.490 <b<0.999

[0040] 0.0 <c<0.5

[0041] 0.0 <s<0.5

[0042] 0.05 <p<0.5

[0043] 0.001 <x<0.01

[0044] 1.0001<(t+a+m)<1.011575

[0045] 0.9889 <t<1.000375

[0046] 0.00010 <a<0.0012

[0047] 0.0001 <m<0.01

[0048] 0.0001 <z<0.01。

[0049] Surprisingly, it is shown that the breakdown voltage can be significantly improved by the doping with R and A according to the present invention, the so-called co-doping with R and A. Without being bound by this interpretation, the inventor believes that, in the case of simple doping with R alone, although the trivalent element R is completely and mainly replaced at the divalent barium position, it is also replaced in small amounts at the tetravalent titanium position. Thus, the donor effect that is sought to be achieved is partially compensated in an undesirable manner. However, the addition of the pentavalent element A offsets this undesirable effect because A is only embedded at the titanium position and is used as an additional donor here. Therefore, co-doping leads to an increased slope of the resistance-temperature characteristic curve (R(T) characteristic curve) of the PTC ceramic, and thus also leads to an increase in the PTC transition and a rise in the breakdown voltage. The addition of lead and / or strontium is used to specifically adjust the phase transition temperature and therefore the temperature of the PTC transition. Pure SrTiO3, for example, crystallizes in a cubic perovskite structure under normal conditions. In the case of pure PbTiO3, the transition from tetragonal to cubic crystal structure occurs only above about 475°C. In addition, during the manufacturing process, a slight excess of titanium can lead to the formation of small amounts of titanium-rich phases, such as Ba6Ti 17 O 40 These compounds act as sintering aids. In addition, an increased excess of titanium in the grain boundary region leads to the formation of barium vacancies, which in turn leads to large PTC jumps. In addition, the addition of manganese leads to receptor levels at the grain boundaries, which particularly favorably influence the PTC properties, so that steeper R(T) characteristic curves and larger temperature-dependent resistance jumps are observed.

[0050] Furthermore, it has proven to be advantageous if the semiconductor ceramic component further contains silicon dioxide, preferably the semiconductor ceramic component contains a minimum of approximately 0.01 weight percent to a maximum of approximately 5 weight percent silicon dioxide, relative to the mass of the entire semiconductor ceramic component, more preferably the semiconductor ceramic component contains a minimum of 0.1 weight percent to a maximum of approximately 1 weight percent silicon dioxide, relative to the mass of the entire semiconductor ceramic component.

[0051] The addition of silicon, preferably in the form of silicon dioxide, leads to lower sintering temperatures during the production process, which primarily results in energy savings. Unlike, for example, Al2O3 or ZrO2, silicon dioxide has the advantage as a sintering aid that it does not have a negative impact on the electrical properties of the product. In addition, it has surprisingly been shown that the breakdown voltage can be advantageously increased as a result.

[0052] In an advantageous embodiment of the semiconductor ceramic composition, R is at least one element selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho and Er, preferably, R is at least one element selected from the group consisting of Y and La, more preferably, R represents the element Y. This results in particularly good PTC properties being achieved.

[0053] In another advantageous embodiment of the semiconductor ceramic composition, A represents the element Nb. This makes it possible to achieve, in particular, an advantageous donor effect.

[0054] Furthermore, it has proven to be advantageous if the variables t, a and m adopt values ​​within the range of the following limits:

[0055] 0.9985 <t<1.000075

[0056] 0.0002 <a<0.0006

[0057] 0.0003 <m<0.001。

[0058] Surprisingly, it has been shown that a particularly advantageous PTC effect is associated with this advantageous composition.

[0059] In particular, it has proven to be advantageous if the variables b, c, s, p, x, t, a, m have the following values:

[0060] b=0.627

[0061] c=0.12

[0062] s=0.03

[0063] p=0.22

[0064] x=0.003

[0065] t=0.999625

[0066] a=0.0003

[0067] m=0.00065.

[0068] Thus, a particularly advantageous chemical composition may have the following stoichiometric formula

[0069] [Ba 0,627 Ca 0,12 Sr 0,03 Pb 0,22 Y 0,003 ][Ti 0,999625 Nb 0,0003 Mn 0,00065 ]O 3,00065 .

[0070] The chemical composition can be determined by chemical analysis methods, for example ICP-OES (Optische Emissionsspektrometrie mit induktiv gekoppeltem Plasma, optical emission spectroscopy with inductively coupled plasma).

[0071] Furthermore, the present invention relates to a semiconductor ceramic including a sintered body having the semiconductor ceramic composition as described above.

[0072] A person skilled in the art understands a sintered body to be a workpiece, for example a ceramic, which is produced during sintering. In this case, for example, a precisely prepared fine-grained ceramic starting material is heated.

[0073] Furthermore, the present invention relates to a method for producing a semiconductor ceramic having a sintered body having the semiconductor ceramic composition as described above, the method comprising the following steps:

[0074] a) Raw material weighing

[0075] b) Mixing and grinding

[0076] c) Drying and pre-granulation

[0077] d) Calcination

[0078] e) Fine grinding

[0079] f) Spray granulation

[0080] g) Suppression

[0081] h) Debinding and sintering.

[0082] In step a), the starting material is first provided and weighed in an accurately defined amount. For example, oxides, carbonates and sulfates, such as TiO2, BaCO3, Pb3O4, Nb2O3, La2O3, MnCO3 or MnSO4 or Mn(CH3COO)2, can be used as starting materials. It has been proven to be advantageous that the starting material is fully dried before weighing, i.e., exists in anhydrous or almost anhydrous form, in order to avoid weighing errors. In addition, the doping element can be added, for example, in the form of chloride, acetate or oxalate, such as YCl3 or Y(CH3COO)3. Here, compared with the addition of chloride, the addition of acetate is advantageously preferred, because the acetate anions are converted into CO2 and H2O without residue during the subsequent treatment, while chloride residues may remain in the product. Typically, after weighing the doping element, it is dispersed in deionized water in order to ensure the uniform distribution of the doping element in the final product. Alternatively, it is also conceivable to add the doping element before fine grinding in step e).

[0083] Next, in step b), mixed grinding is carried out. Here, in a mill with ZrO2 grinding balls, the starting materials are brought to approximately the same particle size and intensively mixed with one another, with the addition of deionized water and possible organic auxiliaries, such as dispersants and PVA (Polyvinalyacetat, polyvinyl acetate) or PVB (Polyvinylbutyral). In this context, for example, a drum mill, a basket mill or a planetary ball mill can be used as a mill. For example, it is conceivable to grind for 4 hours in a planetary ball mill at 200 revolutions per minute and with ZrO2 grinding balls having a diameter of 2 mm.

[0084] In addition, when selecting and weighing the initial material and the crucible material and grinding tool used, it should be noted that impurities containing iron, in particular, have an adverse effect on the desired electrical properties of the PTC material. It is therefore preferred that the possible amount of iron impurities is less than 100 ppm and in particular less than 10 ppm. This also applies to impurities containing alkali metal elements accordingly. For example, it has been proven to be advantageous that the TiO2 initial material has the following impurities at most: K at most 20 ppm, Mg at most 10 ppm, Al at most 20 ppm, Fe at most 10 ppm, Cl at most 100 ppm, Na at most 20 ppm, Nb at most 100 ppm, Zr at most 300 ppm, P at most 100 ppm, S at most 100 ppm, Sb, Ca, V, Co, Ni, Bi, Zn, Cu, B, Cr at most 10 ppm respectively. In order to avoid impurities, it is also conceivable to use plastic coatings in the following places: there, the metal body is in direct contact with the powder and the pressed body used, for example in the grinding container. In addition, it is also conceivable to use particularly wear-resistant materials, such as tungsten carbide or locally hardened materials, for example in the grinding container or the pressing tool.

[0085] Next, in step c), the mixture obtained in step b) is dried. In principle, all methods for drying known to the person skilled in the art are conceivable, for example drying by means of a filter press and in a drying cabinet. Here, typically, the liquid is pressed through the filter paper and the filter residue obtained is subsequently dried. For example, it can be dried in a drying cabinet at about 200° C. for about 14 h. However, it has proven to be advantageous to carry out the spray drying in a spray dryer known to the person skilled in the art. With regard to spray drying, for example, the more detailed explanation further below in the context of step f) applies. This has the advantage that the pre-granular material produced in this way can be processed further more easily. It is conceivable to separate the coarse particle portion from the pre-granular material obtained by means of screening (upper limit of 300 μm).

[0086] After drying in step c), a temperature treatment for calcination is carried out in step d). The powder obtained in step c) is placed, for example, in a calcination capsule and subsequently calcined at an air temperature between 900 and 1200° C. for a period of time between a minimum of about 0.5 h and a maximum of about 4 h. Typical calcination parameters are, for example, 1050° C. for 2 h. During the calcination, the raw powder is thermally decomposed and BaTiO3 is formed as a primary product.

[0087] It is conceivable to carry out the calcination in a chamber furnace in a batch process or in a continuous heating furnace with a ceramic capsule or in a rotary kiln.

[0088] In order to avoid impurities in the product, it is also preferred to use high temperature stable steels for the furnace tubes, such as alloy 600 or alloy 602. For example, yttrium stabilized zirconium oxide capsules or cordierite can be used as ceramic capsules.

[0089] After calcination in step d), fine grinding is carried out in step e). Typically, the fine grinding is carried out in a ball mill. Advantageously, the fine grinding is carried out in deionized water with organic auxiliary agents, such as dispersants, defoamers and polymer binders and PVA or PVB. For example, it is conceivable to fine grind for 6 hours in a planetary ball mill at 200 revolutions per minute and ZrO2 grinding balls with a diameter of 2 mm. For fine grinding, one or more organic pressing binders are supplied to the fine grinding, either immediately at the beginning of the fine grinding or alternatively in the last 15 minutes. Examples of such pressing binders are polyethylene glycol, polyvinyl acetate or methylcellulose. Alternatively, organic auxiliary agents can also be added for a separate re-grinding step.

[0090] Fine grinding is mandatory for subsequent jet granulation.

[0091] Typically, fine grinding is performed to obtain a particle size of approximately <10 μm. 90 , and obtain a d of approximately <3 μm 50 , preferably to obtain a d of about < 2 μm 50 However, it is advantageous to strive to achieve a particle size d of ≤ 1 μm. 50 Grinding is performed inside the material in order to achieve a smaller particle size during sintering, which leads to an increase in the breakdown voltage.

[0092] Diameter value d 50 The following particle diameter is specified: 50% of all particles are smaller than this particle diameter. Conversely, this also means that 50% of all particles have a larger particle diameter. Correspondingly, the diameter value d 90A particle diameter is specified such that 90% of all particles are smaller than the particle diameter. It should be understood that such particles may have a geometry that differs slightly from an ideal sphere. Typically, such particle diameters are determined by means of laser diffraction or automated statistical imaging.

[0093] Next, in step f), spray granulation or spray drying is carried out. In principle, spray drying can be carried out in all spray dryers known to those skilled in the art. For example, the suspension / dispersion can be supplied to the spray dryer by means of a pump. Then, next, the nozzle injection of drying air and dispersion / suspension can be carried out according to the countercurrent principle or the cocurrent principle. Here, the parameters for spray drying can be, for example, an inlet temperature of a minimum of about 170°C to a maximum of about 220°C, a minimum of about 80°C and a maximum of about 110°C for the outlet temperature, and a low negative pressure of about 0.6 kPa. Alternatively, the injection can also be achieved in a rotary spray dryer via a rotating atomizing nozzle (typically 20.000 rpm). The advantage of this is that a particle shape is obtained by additional centrifugal force, which is closer to an ideal spherical shape.

[0094] In the present case, spray drying typically results in a granular material moisture content of approximately <15% and in a granular material size (d 50 ), which is particularly advantageous for homogeneity and introduction and compressibility into a pressing tool. In particular, surprisingly, it has been shown that this also leads to an increase in the breakdown voltage.

[0095] Furthermore, it has proven to be advantageous to use a magnetic filter during the production process in order to avoid or minimize critical metallic impurities.

[0096] Next, in step g), the granular material is pressed. In principle, the pressing can be carried out in all presses known to the person skilled in the art. For example, the dry pressing can be carried out by means of a mechanical linear press having an upper punch and a lower punch, wherein typically a pressure of about 6.6 kN is used in a single piece with a geometry optimized for heating applications. Typical pressing densities are hereby about 3.2 to 3.3 g / cm 3 Alternatively, pressing in a rotary press is also conceivable, for example.

[0097] After step g), in step h), the obtained pressed product is debound and sintered. This can be done in two separate furnaces or in one furnace. Preferably, debinding and sintering are done in one furnace. Here, the furnace can be a sintering furnace with multiple sections, in which there can be a debinding zone, a sintering zone and a cooling zone with a high cavity flow rate. For example, it is conceivable to first pretreat the pressed product at 150 to 400° C. for 2 to 4 hours, depending on the pressing binder used, until all organic residues are removed. Here, slow heating and the resulting avoidance of crack formation have proven to be advantageous for achieving the optimal breakdown voltage. Next, the obtained green body is brought to the sintering zone of the furnace. Typically, sintering is carried out in a ventilated place at a temperature of a minimum of about 1200 to a maximum of about 1400° C., with a holding time of between about 0.5 and 4 hours. Typical sintering parameters are, for example, about 1300° C. for about 1 hour. Next, cooling to room temperature. For example, the cooling can be performed at a cooling rate of a minimum of about 2 K / min to a maximum of about 10 K / min.

[0098] After sintering, grinding to the desired geometry is typically performed on the cooled sintered body. The grinding removes the sintering skin, thereby achieving a more uniform structure and better electrical properties. The grinding must be performed gently in order not to introduce microcracks and in order to reduce the breakdown voltage.

[0099] In addition, the present invention relates to a PTC thermistor having a sintered body and an electrode on a surface of the sintered body, wherein the sintered body has the semiconductor ceramic composition as described above.

[0100] A person skilled in the art understands a thermistor to be a variable and heat-sensitive resistor which has a temperature characteristic which is nonlinear and whose value changes in a reproducible manner with temperature. In the present case, a sintered body having a semiconductor ceramic composition as described above has metallization on two opposite sides. The metallization is used for electrical contacting.

[0101] In principle, all metallization layers known to the person skilled in the art are conceivable, which can be used for electrical contacting on the surface of the sintered body. It has proven to be particularly advantageous if the metallization has a Cr layer on the sintered body and a further layer located on the Cr layer, the Cr layer having a thickness of approximately 0.1 μm, the further layer located on the Cr layer consisting of nickel or a nickel alloy and having a thickness of approximately 0.4 μm. It has also proven to be advantageous if the metallization additionally has a layer having Ag as a main component and located on the layer consisting of nickel or a nickel alloy, the layer having a thickness of approximately 7 μm. Advantageously, the Cr layer and the layer consisting of nickel or a nickel alloy are applied by means of a PVD method. Advantageously, the layer having Ag as a main component is also applied by means of screen printing and subsequent firing.

[0102] Of course, the thickness and shape of the PTC semiconductor ceramic can be selected depending on the desired application. For example, it has proven to be advantageous to use a thickness of about 2 mm for an operating voltage of about 350 V and a thickness of, for example, about 2.8 mm at most to about 2.5 mm at least for an operating voltage of 800 V for use in a heater, preferably a thickness of about 2.5 mm is used at an operating voltage of about 800 V. Typically, the PTC semiconductor ceramic described above has a ρ(T) profile in the small signal range of ≤1.5 V (so-called measurement at low voltage), such as Figure 5 shown.

[0103] Furthermore, the present invention relates to the use of a semiconductor ceramic having the semiconductor ceramic composition as described above in a high-voltage heating application, a switching element, a measuring element or a temperature control element. Preferably, the semiconductor ceramic is used in a high-voltage heating application.

[0104] In this context, high-voltage applications are to be referred to as use as PTC heating elements for vehicles with high onboard voltages of at least approximately 350 V and preferably ≧800 V.

[0105] Furthermore, use as an overvoltage protection device, as a switch with hysteresis possibility, as an overtemperature protection device or as a switching current limiter is conceivable. BRIEF DESCRIPTION OF THE DRAWINGS

[0106] Further important features and advantages of the invention emerge from the dependent claims, the drawings and the associated description of the figures and the examples.

[0107] It is self-evident that the features mentioned above and those yet to be explained below can be used not only in the respectively specified combination but also in other combinations or alone without departing from the scope of the present invention.

[0108] Figure 1 : A general schematic representation of the voltage-current intensity characteristic curve of a PTC component.

[0109] Figure 2 : Schematic representation of an example of a semiconductor ceramic having a metallization on two opposite sides.

[0110] Figure 3 : Schematic diagram of a method for manufacturing a semiconductor ceramic according to the present invention.

[0111] Figure 4 : Schematic diagram of the high pressure air heater.

[0112] Figure 5 : Typical curve of the resistivity ρ as a function of the temperature T for a PTC ceramic according to the invention. DETAILED DESCRIPTION

[0113] Figure 1 A schematic diagram showing a typical voltage-current intensity characteristic curve of a PCT component is shown. R It is the nominal voltage, such as 350V or 800V, for which the PCT ceramic is designed. max is the maximum voltage applied when the battery is fully charged. re Represents when U is applied max The corresponding maximum current flowing when BD Represents the breakdown voltage.

[0114] Figure 2 a) shows by way of example a PTC semiconductor ceramic according to the semiconductor ceramic composition proposed in the present application, which has a sintered body 201. In this case, the semiconductor ceramic 201 is coated on two opposite sides with a metal layer 202, which can be used for electrical contacting. Figure 2 b) and Figure 2 c), it is not only possible to consider a cylindrical arrangement (disk) but also a box-shaped arrangement (cuboid). In this context, it should be noted that Figure 2 In c), the metal layer is also present on two opposite sides, one side not being shown in this schematic perspective view. Advantageously, a cuboid shape is used.

[0115] Figure 3In method step a), the raw material weighing 300 is first shown. It is conceivable that all the weighed starting materials are mixed in the following step b). However, it is alternatively conceivable, for example, to add doping elements and / or SiO2 only in step e). In step b), mixed grinding 301 is carried out. Next, drying and pregranulation 302 are carried out in step c). In step d), the previously obtained granular material is calcined 303. Subsequently, fine grinding 304 is carried out in step e). If not all the weighed starting materials have been added in step b), the remaining starting materials are now added in step e). Preferably, after fine grinding 304, there is a particle size d of approximately <10 μm. 90 , and there is a d of approximately <3 μm 50 , preferably with a d of about < 2 μm 50 Particularly preferably, the particle size d 50 ≤1 μm. Subsequently, in step f), spray granulation 305 is carried out. Preferably, this results in a granular material moisture of approximately <15% and in a granular material size (d 50 ). Then, in step g), extrusion 306 is performed, followed by debinding and sintering 307 in step h).

[0116] Unless otherwise stated, for all method steps a) to h) what has already been explained above in the context of the method steps applies.

[0117] Optionally, in a further step, it is conceivable that the obtained and cooled sintered body is ground into the shape required for the desired application. In addition, optionally, metallization 309 can be performed after grinding, that is, a metal layer is applied on two opposite sides of the sintered body, which metal layer can realize electrical contact connection.

[0118] Figure 4 The structure of the high-voltage air heater is schematically shown. Here, the PTC heating element 403 is contacted by the Al contact foil 400. The two elements are insulated by the Al2O3 insulating part 401 and are located in the Al tube 402 in the form of a bonded PTC heating element 405, which has a contact connection part and an insulating part. Six such modules are electrically connected to each other 406 and can be loaded into a housing 407. Together with the control device and the attachment end, an element 408 is produced. This element is equipped with a cover device for the control unit and produces an electric PTC heater 409 ready for use.

[0119] Figure 5The typical curve of the resistivity of the PTC ceramic according to the invention as a function of temperature (ρ(T) curve) is shown. The geometry of the PTC ceramic is calculated. Here, as mentioned above, a strong increase in the resistivity can be seen in the range of the phase transition.

[0120] Hereinafter, the present invention is described in detail based on examples without limiting the scope of the present invention thereto:

[0121] Materials used:

[0122] BaCO3, CaCO3, SrCO3, Nb2O5, Y2O3, PbO2, TiO2, Mn(CH3COO)2, SiO2

[0123] Example IE1 according to the present invention

[0124] A semiconductor ceramic having the following semiconductor ceramic composition is produced.

[0125] [Ba b Ca c Sr s Pb p R x ][Ti t A a Mn m ]O 3+z .

[0126] in,

[0127] R: Y

[0128] A: Nb

[0129] b: 0.627

[0130] c: 0.12

[0131] s: 0.03

[0132] p: 0.22

[0133] x: 0.003

[0134] t: 0.999625

[0135] a:0.0003

[0136] m: 0.00065

[0137] z: 0.00065

[0138] and 0.3 weight percent SiO2.

[0139] implement:

[0140] First, the starting materials BaCO3, CaCO3, SrCO3, Nb2O5, Y2O3, PbO2, and TiO2 were weighed. Then, they were mixed and ground in a planetary ball mill in a suspension consisting of deionized water for 4 h (200 R / min; grinding balls: ZrO2, ). Then, the powder was crushed and screened, dried in a drying cabinet at a temperature of 120° C. for 14 h and calcined at 1000° C. for 2 h.

[0141] Subsequently, Mn(CH3COO)2 was added. Furthermore, SiO2 was added in a proportion of 0.3% by weight relative to the total composition. The mixture was then finely ground in a planetary ball mill (duration: 6 h; 200 revolutions / min, grinding balls: ZrO2, ). In contrast to the mixed grinding, the grinding is carried out in a suspension with isopropanol. In the fine grinding, a binder (PVB) is also added to the suspension. The subsequent spray drying is carried out at a gas inlet temperature of 170° C. and a gas outlet temperature of 85° C. After the spray granulation, the d 90 The particle size is 74 μm and the bulk density is 1.28 g / cm 3 .

[0142] The obtained granular material was extruded by uniaxial pressing to a pressure of about 3.4 g / cm 3 The sintering was carried out at T=1300° C. and a holding time of 1 h using a sintering aid consisting of zirconium oxide.

[0143] The sintering skin of the resulting green body was then ground off and cleaned with deionized water and isopropanol. To make contact, a layer (thickness: about 10 μm) was applied to the end faces of the ground sintered body with Al paste. The layer was dried at 150° C. for 15 minutes and then burned out at 720° C. for 15 minutes.

[0144] Then, the portion connected by the Al contact is electrically measured, that is, the ρ-T curve of the portion is measured (see Figure 5 ).

[0145] Reference numerals list

[0146] I re : Maximum current (at U max In the case of

[0147] U R : Nominal voltage

[0148] U max : Maximum voltage

[0149] U BD : Breakdown voltage

[0150] 201: Semiconductor Ceramics

[0151] 202: Coating with electrodes

[0152] 300: Raw material weighing

[0153] 301: Mixed grinding

[0154] 302: Drying and pre-granulation

[0155] 303: Calcination

[0156] 304: Fine grinding

[0157] 305: Injection granulation

[0158] 306: Suppression

[0159] 307: Debinding and sintering

[0160] 308: Grinding

[0161] 309: Metallization

[0162] 400: Al contact foil

[0163] 401: Al2O3 insulation part

[0164] 402: Al tube

[0165] 403: PTC heating element,

[0166] 404: A bonded PTC heating element having a contact portion and an insulating portion

[0167] 405: Encapsulated, bonded heating element

[0168] 406: Six bonded and electrically connected modules of element 405 shown previously

[0169] 407: Module in housing

[0170] 408: Module in housing with control device and attachment terminal

[0171] 409: Module with control device cover as shown below 408; electric PTC heater ready for use

Claims

1. Semiconductor ceramic components, including: The semiconductor ceramic composition has as a main component a BaTiO3-based compound according to the following molecular formula: [Ba b Approx c Sr s Pb p R x ][Ti t A a Mr m ]O 3+z , wherein R is at least one element selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb, wherein A is at least one element selected from the group of V, Nb, and Ta, wherein variables b, c, s, p, x, t, a, m, and z are defined as follows: b=1–c–s–p–x 0 <c+s+p<0.51 0.490<b<0.999 0.0<c<0.5 0.0<s<0.5 0.05<p<0.5 0.001<x<0.01 1.0001<(t+a+m)<1.011575 0.9889<t<1.000375 0.00010<a<0.0012 0.0001<m<0.01 0.0001<z<0.01。 2. The semiconductor ceramic composition according to claim 1, characterized in that: The semiconductor ceramic composition further comprises silicon dioxide. Preferably, the semiconductor ceramic composition comprises a minimum of about 0.01 weight percent to a maximum of about 5 weight percent of silicon dioxide relative to the mass of the entire semiconductor ceramic composition. More preferably, the semiconductor ceramic composition contains a minimum of 0.1 weight percent to a maximum of about 1 weight percent of silicon dioxide relative to the mass of the entire semiconductor ceramic composition.

3. The semiconductor ceramic composition according to any one of claims 1 and 2, characterized in that: R is at least one element selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho and Er. Preferably, R is at least one element selected from the group consisting of Y and La. More preferably, R represents element Y.

4. The semiconductor ceramic composition according to any one of the preceding claims, characterized in that A represents the element Nb.

5. The semiconductor ceramic composition according to any one of the preceding claims, characterized in that The variables t, a and m take values ​​within the range of the following limits: 0.9985<t<1.000075 0.0002<a<0.0006 0.0003<m<0.001。 6. The semiconductor ceramic composition according to any one of the preceding claims, characterized in that The variables b, c, s, p, x, t, a, and m take the following values: b=0.627 c=0.12 s=0.03 p=0.22 x=0.003 t=0.999625 a=0.0003 m=0.00065。 7. A semiconductor ceramic comprising a sintered body having the semiconductor ceramic composition according to any one of the preceding claims.

8. A method for producing a semiconductor ceramic having a sintered body, the sintered body having the semiconductor ceramic composition according to any one of claims 1 to 6, the method comprising the following steps: a) Raw material weighing b) Mixing and grinding c) Drying and pre-granulation d) Calcination e) Fine grinding f) Spray granulation g) Suppression h) Debinding and sintering.

9. A PTC thermistor, the PTC thermistor comprising: - a sintered body having a semiconductor ceramic composition according to any one of claims 1 to 6, and - an electrode on the surface of said sintered body.

10. Use of a semiconductor ceramic having the semiconductor ceramic composition according to any one of claims 1 to 6 in high voltage applications, switching elements, measuring elements or temperature control elements, preferably, the semiconductor ceramic is used in high voltage heating applications.

Citation Information

Patent Citations

  • Current collector for lithium-ion battery, preparation method of current collector, pole piece for lithium-ion battery and lithium-ion battery

    CN107611447A

  • Ceramic dielectric, method of manufacturing the same, ceramic electronic component and electronic device

    CN110246689A

  • PTC thermistor ceramic material as well as preparation method and application thereof

    CN112694325A

  • Current collector and application thereof

    CN113644276A

  • Preparation method of ceramic PTC thermistor material

    CN114560694A